A benchmarking approach to the progress of green materials and systems' use in the UAE construction industry. Issue 4 (3rd October 2016) - Elgayar, Aly; Beheiry, Salwa Mamoun; Jabbar, Alaa; Al Ansari, Hamad
Abstract : Purpose: Over the past decade, the United Arab Emirates (UAE) introduced several green regulatory guidelines, federal decrees, and a considerable number of environmentally friendly initiatives. Hence, the purpose of this paper is to investigate the top green materials and systems used currently in the UAE construction industry as per the new laws dictate as well as see if professionals are switching over to incorporate more green materials, systems, and/or designs. Design/methodology/approach: The work involved reviewing internationally popular green materials and systems for construction, developing a questionnaire based on the literature review, surveying professionals in the seven UAE emirates, and ranking the findings based on the relative importance index. Findings: Findings found the top used green materials and system in the UAE's construction industry. As well as identified that there is a communication gap between the design and implementation phases that is possibly hindering the use of more green materials and systems. Originality/value: This study sets a baseline to measure the UAE's progress over the coming years in terms of integrating more green construction materials, systems, methodologies, and trends.